Kajian Sifat Kuantitatif Galur F2 Tanaman Jagung di Lahan Kering: Study of the Quantitative Characteristics of the F2 Line of Corn Plants on dry land - I Wayan Sudika; I Wayan Sutresna; Dwi Ratna Anugrahwati; Lestari Ujianto (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
This study was aimed to determine the average of leaf angle, yield and harvest age of each F2 line compared to the two parents respectively. In addition, we also want to evaluate the coefficient of genetic diversity and heritability of the three traits. The experiment was designed in a randomized block design with a total treatment of 20 populations, namely 16 F2 lines and 4 parents. Each treatment was repeated 3 times, so that 60 experimental units were obtained. The experimental data were analyzed by analysis of variance at the 5 percent significance level and further tests using the Least Significant Difference at the same significance level. The results showed that the F2 P8IS x T1NK7328 (R16), F2 P8IS x T1NK7328 (R18) lines, and the F2 P8IS x NK212 (R4) lines, had leaf angles same as each parent of the first hybrid/hybrid offspring (T1NK7328 and NK212) and smaller than the Sinta Unram. The harvest time of the three F2 lines was classified as super early. Yield (weight of dry seeds per plot) of F2 P8IS x T1NK7328 (R16), F2 P8IS x T1NK7328 (R18) lines, were the same as both parents and F2 P8IS x NK212 (R4) lines, higher than Sinta Unram; but the same as the hybrid parent (NK212). Coefficient of genetic diversity of yield is high; medium for harvest time and low for leaf angle. Heritability in broad sense is classified as high, obtained at harvest time and yield; while the heritability of leaf angle is low. The three F2 lines can be used as basic population material for subsequent breeding activities. Key words: hybridization; Sinta Unram; yield; leaf angle